흰점박이꽃무지 유충(Protaetia brevitarsis seulensis Larvae) 열수 추출물의 MAPKs 및 NF-κB 신호전달을 통한 대식세포 내 면역 활성 효과 - 유보경(Bo-Gyeong Yoo); 홍준표(Jun-Pyo Hong); 송하연(Ha-Yeon Song); 변의홍(Eui-Hong Byun) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2022)
본 연구는 흰점박이꽃무지 유충 열수 추출물(PLW)의 면역 활성 효과에 대해 알아보기 위하여 선천면역에서 중추적인 역할을 하는 대식세포인 RAW 264.7에 PLW를 처리하여 세포 생존율, cytokine(TNF-α 및 IL-6), NO 분비능과 세포 표면 활성 인자의 발현 증가량을 관찰하고, 세포 내 기전을 해석하였다. PLW를 RAW 264.7 세포에 처리하였을 때 cytokine과 NO의 분비능이 PLW 처리군에서 유의적으로 증가하였고, 세포 표면의 CD80, CD86 및 주조직적합성복합체(MHC class Ⅰ과 II)의 발현도 유의적으로 증가하는 것을 관찰할 수 있었다. 또한 PLW 처리에 의한 대식세포의 면역 활성이 MAPKs의 인산화 및 NF-κB의 핵 내 전사에 의한 것임을 확인하였다. 종합적으로 PLW의 처리는 MAPKs의 인산화 및 NF-κB의 전사를 유도하여 염증 매개 인자들을 효과적으로 발현시키고, 이를 바탕으로 RAW 264.7 대식세포의 면역 활성을 유도하는 것으로 관찰되었다. 이러한 연구결과는 흰점박이꽃무지 유충 열수 추출물이 면역증강 기능성 소재로 유용하게 활용될 수 있다는 가능성을 제시한다. Protaetia brevitarsis seulensis (P. brevitarsis) larvae have traditionally been used in alternative medicine. Although various health benefits have been reported, the immunomodulatory effects of P. brevitarsis extract have so far been unknown. In this study, the immune-enhancing activities of P. brevitarsis larvae hot-water extract (PLW) were investigated using the RAW 264.7 macrophage cell line. The PLW did not exert cytotoxicity at concentrations ranging from 1 to 200 μg/mL in RAW 264.7 cells. The treatment of PLW increased the production of nitric oxide and cytokines [tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6)] at doses of 100, 200 μg/mL in RAW 264.7 cells. Additionally, treatment with PLW (100, 200 μg/mL) led to the increase of surface molecules (cluster of differentiation; CD80/86 and major histocompatibility complex; MHC-class Ⅰ/Ⅱ) expression in RAW 264.7 cells. These immunomodulatory effects of PLW were mediated by mitogen-activated protein kinases (MAPK-extracellular signal-regulated kinase, c-Jun N-terminal kinase, p38 MAPK) phosphorylation and nuclear factor (NF)-κB translocation. In conclusion, these findings provide experimental evidence that PLW can be used as an immunity-enhancing nutraceutical ingredient. KCI Citation Count: 6